Analisis Risiko Keselamatan dan Kesehatan Kerja di PT X dengan Metode HIRARC - Maryam, Aghitsna Fyisayyidah; Herwanto, Dene; Debora, Fransisca (Universitas Indraprasta PGRI Jakarta, 2025)
Occupational health and safety (OHS) is a top priority in the construction industry due to the high risk of workplace accidents, often caused by negligence or unsafe environmental conditions. This study aims to identify potential hazards in the workplace, assess the risk levels posed by these hazards, and develop control measures to create a safer work environment. The method used is Hazard Identification, Risk Assessment, and Risk Control (HIRARC). The results show that the application of the HIRARC method is effective in identifying various potential hazards in the workplace and providing appropriate control recommendations to reduce the risk of accidents. These control recommendations include preventive measures that the company can implement to enhance worker safety. This study not only helps the company improve its occupational health and safety performance but also contributes valuable insights to the field of OHS. In conclusion, the implementation of the HIRARC method plays a crucial role in minimizing workplace accident risks and creating safer and healthier working conditions in the construction industry.